(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Within the European Union’s Seventh Framework Programme project “Enhancing of legumes growing in Europe through sustainable cropping for protein supply for food and feed” (EUROLEGUME) producing of the knowledge required for the implementation of legume supported cropping system in sustainable agriculture was done. The main objective of this study was to investigate spring cereal species effect on protein content in pea grains depending cropping system (organic and conventional). The research involved two field pea (Pisum sativum var.arvense L.) cultivars – ‘Kirke’ and ‘Bruno’, and two spring cereal species: spring wheat (Triticum aestivum L.) and oat (Avena sativa L.) grown in mixtures. The results demonstrated that in pea-cereal mixtures cereal species can affect the protein content of grains of pea. Depending cultivar the effect was different. In grains of cv ‘Bruno’ crude protein content was highest; the higher the protein of grains fixed in yield from organic field.